Reshaping anisotropic gold nanoparticles through oxidative etching: the role of the surfactant and nanoparticle surface curvature. Issue 9 (23rd December 2014) - Yuan, Haifeng; Janssen, Kris P. F.; Franklin, Thomas; Lu, Gang; Su, Liang; Gu, Xian; Uji-i, Hiroshi; Roeffaers, Maarten B. J.; Hofkens, Johan
Abstract : We study reshaping of gold nanorods, bipyramids and triangles to reveal roles of the surfactant in the oxidative etching process. Abstract : We report an investigation on the effect of stabilization agents and surface curvatures on oxidative etching of three classes of anisotropically shaped gold nanoparticles namely, rods, bipyramids and prisms. In particular, the dual role of the stabilizing agent CTAB in the etching process is explored, showing how it acts both as a source of bromine ions, accelerating etching and as a protection agent, resulting in anisotropic reshaping.